Antioxidant, anti-urease and anti-elastase activities of Usnea longissima Ach. (Bangladesh Journal of Botany, 2018)
Lichens are complex associations composed of mycobiont and one or more algae or cyanobacteria which are living in symbiosis. Lichens are thought to possess therapeutic effects on many illnesses in worldwide. This study was performed to investigate antioxidant, anti-elastase and anti-urease activities of Usnea longissima Ach lichen. U. longissima was extracted with ethanol and ethyl acetate solvents. The antioxidant activities of the extracts of U. longissima were determined with methods such as 1,1-diphenyl-2- picrylhydrazyl (DPPH) radical scavenging activity, 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical scavenging activity, copper reducing antioxidant capacity (CUPRAC), total antioxidant capacity, determination of total phenolic content and total flavonoid contents. The binding action of the DPPH and ABTS radicals, CUPRAC activity increases with concentration of the extracts. Ethanol extracts exhibited higher anti-urease and anti-elastase activity. Highest inhibition was found as 49.86% for elastase and 18.38% for urease. Results of the present study suggest that U. longissima extracts can be an alternative to synthetic antioxidant, anti-elastase and anti-urease agents.